Future agricultures: The promise and pitfalls of a (re)turn to nature. (March 2022) - Sumberg, James
This paper introduces the Outlook on Agriculture Special Issue on biomimicry and nature-based solutions. It provides a selective overview that will help frame and situate the collection, with a particular focus on agriculture and food production. The relationship between agriculture and nature is a central concern, and particularly how this relationship is framed by those promoting the idea that to overcome the multiple challenges it faces, agriculture must (re)turn to nature. The significance of different understandings of 'nature-based solutions', and the relative importance of biomimicry, are explored.